A new character-level encryption algorithm: how to implement cryptography in an ICT classroom - Arboledas Brihuega, David (Journal of Technology and Science Education, 2019)
It is evident that the society in which we live will demand more and more qualified and specialized positions in the different branches of engineering. Now we are in a highly digitized world in which information is continuously transmitted through data communication networks with the expectation of security and confidentiality. Students who are in their last year at high school face the problem of deciding their professional future. Therefore, there is a wide field of research for them in cryptographic techniques. In this work we have developed, together with a group of high school students, a cryptographic algorithm with substitution and transposition techniques as described by Feistel (1973) in order to create a more comprehensive knowledge about what they have been studying in their ICT subjects. In most cases the teaching methods are based on the teachers' own vision, as well as on the absence of knowledge of alternative methods and/or the impossibility of applying them physically in the classroom. With the active and cooperative methodology put forward in this work, objectives such as hard work, autonomous and collaborative learning and the exchange of knowledge have been absolutely fulfilled. Achieving them requires replacing traditional methods so that the student can adapt to new work challenges. A group of students, only three of whom finished, were voluntarily provided with the mentoring service in which the algorithm was designed. As a result, we were able to program in Python as a final project a symmetrical character-level encryption algorithm we've referred to as Azrael. Our findings indicate a demand for future endeavours to take into account the need for more projectbased work in ICT classrooms. The exchange of ideas between teacher and students has been the driven force behind the success of this activity